Economia da defesa naval, poder naval e efeitos dos investimentos - Pinto, Guilherme Penha (2019)
In Brazil the Defense Economics is a topic that demands a deepening of the theoretical and empirical discussions, in particular, about the role of the public policies for the National Defense, starting from the debate of the investments in the Armed Forces, interacting with the other expressions of the Power Brazilian National. Therefore, the purpose of this thesis was to simulate investments in the strategic projects of the Brazilian Naval Power, based on the knowledge of the historical, political and strategic scenario of that country. From an Input-Output Matrix (IOP) for the Brazilian Defense Sector, an unprecedented model of a General Computable Equilibrium (GCE) for that country, called ORANI-G, was adapted to a GCE model adhering to the evaluation of fiscal policies. The model showed great capacity in generating results in terms of public policy achievements, according to the empirical literature on the evaluation of investments in Defense in international literature, and also demonstrated that the performance of the main macroeconomic variables of the Brazilian economy improved significantly due to the net effect of the investment policy in Defense. The consolidation of the National Power, through investments in the Naval Power, provided a rise in variables such as real GDP growth, exports, real household consumption, aggregate employment, imports, real wages and other economic costs.